Explaining ?Unexplained Visual Loss? with Optical Coherence Tomography - Sumaira Amir Joya, Maria Akhtar, Hina Khan, Aamir Asrar, Muhammad Siddique (Pakistan Journal of Ophthalmology, 2016)
Purpose: To determine various pathologies detected by Optical Coherence Tomography (OCT) in patients with Unexplained Visual Loss (UVL).Study Design: A retrospective case review.Place and Duration of Study: Amanat Eye Hospital from October 2014 to October 2015.Material and Methods: All cases of UVL were scanned on Heidelberg Spectralis Spectral Domain OCT machine on EDI mode. The scans so obtained were evaluated for a possible pathology that was responsible for the visual loss. Frequency tables were charted on this basis.Results: 83 patients with unexplained visual loss and apparently normal fundi were reviewed. In 37 cases, a definitive diagnosis was provided with the help of OCT imaging. 10 (27.03%) patients showed vitreomacular traction, 5 (13.51%) showed epiretinal membranes, 4 (10.81%) showed early stages of macular hole, 2 (5.4%) showed lamellar holes, 3 (8.1%) showed idiopathic macular telangiectasia, 4 (10.81%) were children with cone dystrophy and there were single cases (2.7%) each of Juvenile X- linked Retinoschisis, retinal arteritis, Acute macular neuroretinopathy and solar maculopathy. 5 (13.51%) patients showed a selective foveal atrophy of one or both eyes but the cause could not be determined. 46 patients with unexplained visual loss showed a normal OCT.Conclusion: OCT was able to identify various retinal pathologies in patients with UVL that was missed on fundus exam. With its help, a wide fraction of patients labeled with UVL were excluded from this obscure diagnosis.Key Words: Visual loss, ocular coherence tomography, Vitreo-retinal diseases.